(untitled) (Journal of Universal Science Research, 2025)
This paper explores the specific challenges encountered in teaching English as a foreign language to students with sensory impairments – namely, hearing, vision, and speech difficulties – within inclusive educational settings aims to ensure equitable access to learning for all students, those with sensory disabilities often face barriers that require adapted and specifically designed methodologies. Drawing from academic research and practical strategies, this study sheds light on main obstacles and suggests better approaches to better support English language learners with diverse needs.